The Influence of the Creative Problem-Solving (CPS) Model on Students’ Learning Motivation and Mathematical Problem-Solving Ability - Anisa Risanda Damanik; Tanti Jumaisyaroh Siregar (MASI Mandiri Edukasi, 2025)
This study tries to find out if using the Creative Problem Solving (CPS) model can improve the learning motivation and math problem-solving skills of eighth-grade students at MTs Akbar Insan Cendikia during the 2024/2025 school year. The study used a Quasi-Experiment method with a pre-test and post-test design that included both an experimental group and a control group. A total of 60 students were chosen through a purposive sampling method, with class VIII-A serving as the experimental group and VIII-B as the control group, each having 30 students. The tools used to collect data were a questionnaire to measure learning motivation and a test to assess problem-solving abilities. The data was analyzed using a t-test after checking for pretest scores, normality, and homogeneity. The results showed that the CPS model had a strong impact on increasing students' learning motivation, as the t-value obtained was 2.472, which is higher than the t-value from the table (2.002). It also had a significant effect on improving students' math problem-solving skills, with a t-value of 2.250, again higher than the t-value from the table (2.002). These findings show that the Creative Problem Solving model can be a good and effective method to enhance math learning in secondary schools.